Optimization of capital structure with cost of capital as a measurement - Trisnaningsih, Sri; Hendra, Failasuf Herman (Future Science, 2020)
The purpose of the present study was to prove that the weighted average cost of capital can be used as a measurement of capital structure optimization. The sample was nine food and beverage companies listed in the Indonesia Stock Exchange from 2015 to 2019 taken secondary data were used with a quantitative approach. Hypotheses were tested by using multiple linear regression analysis. Analysis showed that simultaneously had significant effects on the cost of capital. Partial analysis showed that the debt to asset ratio affected the cost of capital. The long-term debt to equity ratio and net profit margin partially did not affect. Comparison of means showed that return on investment was lower than the means of the WACC. Thus, it can be concluded that the weighted average cost of capital can be used as a benchmark of capital structure optimization with the weighted average cost of capital as the minimum rate of return on investment.